Bezold-Jarisch Reflex Induced by Dopamine during Isoflurane Anesthesia in Small Dogs - Oh, Sang Yub; Hwang, Soonpil; Seo, Hyuk Soo; Lee, Seungju; Kim, Hwi-Yool (Acta Scientiae Veterinariae, 2022)
Background: Unlike other major reflexes contributing to hemodynamic homeostasis, the Bezold-Jarisch reflex (BJR) paradoxically decreases heart rate (HR) and mean arterial pressure (MAP) despite hypotension. In the veterinary field, there are few reported cases of BJR induced by dopamine, which is often used to manage hypotension. Herein, 2 cases involving small dogs exhibiting BJR due to dopamine infusion during general anesthesia are described. Cases: Case 1: A 7-year-old, 7 kg, mongrel was referred for external skeletal fixator removal. The patient was premedicated with 0.3 mg/kg midazolam and 0.2 mg/kg butorphanol intravenously (IV). General anesthesia was induced with 6 mg/kg propofol and maintained with 1.6% isoflurane in oxygen. The patient was given 5 mL/kg/h of Hartmann’s solution IV. The respiratory rate (RR) was set to 9 breaths/min with a ventilator. The HR and MAP values were initially 120 bpm and 76 mmHg and gradually decreased to 70 bpm and 40 mmHg, respectively. The end-tidal CO2 partial pressure (ETCO2) was 39 mmHg, and the patient was administered 2.5 μg/kg glycopyrrolate IV. Then, 5 μg/kg/min dopamine was administered IV since the MAP did not improve. The HR, MAP, and ETCO2 increased to 113 bpm, 72 mmHg, and 47 mmHg, respectively. Subsequently, HR and MAP dramatically decreased to 50 bpm and 43 mmHg, respectively. A second-degree atrioventricular block was detected, prompting dopamine infusion discontinuation, and 2.5 μg/kg glycopyrrolate was again administered IV. Within 5 min, HR and MAP values normalized, and postoperative patient recovery was typical. Case 2: A 2-year-old, 8.6 kg, mongrel underwent surgery to correct a medial luxating patella of the right leg. The patient was premedicated with 0.3 mg/kg midazolam and 0.2 mg/kg butorphanol IV. Anesthesia was induced with 4 mg/kg propofol IV and maintained with 3% isoflurane in oxygen; 10 mL/kg/h of Hartmann’s solution was administered IV. Within 15 min, the patient’s HR and MAP values decreased from 120 to 107 bpm and 73 to 50 mmHg, respectively. The ETCO2remained approximately 39 mmHg, and RR decreased from 20 to 17 breaths/min. Dopamine was infused at a rate of 5 µg/kg/min. After 10 min, the MAP slightly increased from 50 to 57 mmHg, but the HR dramatically decreased from 107 to 62 bpm and the RR also dropped to 12 breaths/min. Further, a second-degree atrioventricular block was observed. Dopamine infusion was immediately discontinued, and 2.5 μg/kg glycopyrrolate was injected IV. As the HR returned to 94 bpm, the atrioventricular block disappeared, and the RR increased to 15 breaths/min. After general anesthesia was terminated, the patient recovered well. Discussion: Among drugs used for anesthesia, propofol and isoflurane may lower the MAP and HR. Therefore, HR or MAP decreases at the beginning of anesthesia are likely due to the drugs. Considering half-life, it is unlikely that propofol provoked sudden HR or MAP decreases at about 25 min post-induction. Isoflurane may also be ruled out since the hemodynamic disorder depended on dopamine injection. Sudden decreases in the HR, MAP, or RR after dopamine injection are not generally expected dopaminergic or adrenergic responses, which likely occur due to the vagal cardiopulmonary reflex suggesting the BJR resulting from activation of cardiac mechano- or chemoreceptors. To the best of our knowledge, there have been no reports of dopamine-mediated BJR in young or middle-aged, small dogs. The BJR has been observed in older, larger dogs and humans. In the patients described, body condition score may be considered when estimating the cause of the BJR. Since they scored 8/9, it is possible that obesity increased the risk of the BJR. This report described the clinical features and treatment outcomes in young or middle-aged, obese, small-sized dogs, whose hypotension or bradycardia was exacerbated by dopamine. Keywords: Bezold-Jarisch reflex, dopamine, hypotension, bradycardia, canine.